Four-stroke performance tuning - Bell, A. Graham (Sparkford, UK : Haynes Pub., 2006)
First published in 1981 and regularly reprinted since, this remains one of the most comprehensive works available to the enthusiast engine tuner and race engine builder. Drawing on his practical experience in tuning and modifying high-performance road, rally and race units, it sets out in detail the many prionciples involved in tuning four-stroke engines. A. Graham Bell explains and analyses every aspect of an engine's operation in this illustrated book.
Includes index.
Second edition published by Haynes 1998. First edition published by G.T. Foulis & Co. 1981 under the title: Performance tuning in theory and practice : four strokes.
Keywords: Automobiles -- Motors -- Maintenance and repair -- Amateurs' manuals; Automobiles -- Motors -- Modification -- Amateurs' manuals; Motor vehicles -- Motors; Motorcycles -- Motors -- Maintenance and repair -- Amateurs' manuals; Motorcycles -- Performance